84 Safety of Selective Early Discharge Following Transcatheter Aortic Valve Implantation. (31st May 2014) - Parry-Williams, Gemma; de Belder, Mark; Bandali, Alykhan; Andrew Owens, W; Andrew Goodwin, Douglas Muir
Abstract : Introduction: Transcatheter Aortic Valve Implantation (TAVI) is being used increasingly in patients with severe symptomatic Aortic Stenosis (AS). There are few data on length of stay (LOS) in this elderly and co-morbid population. This study evaluates the safety of selective early discharge post TAVI. Methods: Data were collected prospectively on all 121 patients who underwent TAVI between 2009 and October 2012. Subjects with severe symptomatic AS were selected for TAVI by the heart team if they had logistic Euroscore >20 and/or were deemed inoperable after direct surgical review. All patients received an Edwards Sapien or Sapien XT valve via transfemoral (n = 89), trans-apical (n = 23) or direct aortic (n = 9) routes. Complications (VARC-2 criteria), LOS and 30 day re-admissions were recorded. Pre-defined minimum LOS was discharge on day 3 post TAVI. Patients were divided into early (<day 4) and delayed discharge groups. Results: Median LOS was 4 days. 40% of patients had been discharged by day 3 post TAVI and 61% by day 4. Transfemoral patients had a significantly shorter median LOS than other routes (3 days vs 6.5 days, p = 0.001). The overall early (30 day) re-admission rate was 10/121 (8.3%). There was no significant difference in re-admissions between the early and delayed discharge groups (9.5% vs 6.4%). There were no deaths between discharge and 30 days and no patients required readmission for PPM. Discussion: This study suggests that selective early discharge post TAVI is not associated with higher rates of readmission, sudden death or PPM. Mean LOS of 6 days compares favourably to data from other centres reporting mean LOS of 6.8–15 days. Other studies have recorded readmission rates of between 8–15% so our policy of selective early discharge does not appear to be at a cost of higher readmission. Re-admission rate was lowest in our transfemoral group at 5.6%. Conclusion: Selective early discharge following TAVI appears to be safe and is not associated with increased early readmission or delayed complications.